The Importance of Islamic Education Teachers’ Performance Assessment in Realising High Quality Of Madrasah - Lilik Huriyah; Ali Mudlofir; Moh. Ali Aziz; Muhammad Anas Ma'arif; Siti Amaliati; Yusrianingsih (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – Teacher performance assessment is a very important element for madrasah to improve quality. This research aims to explore the planning, implementation, evaluation, and impact of performance assessment for Islamic education teachers at State Islamic Senior High School Surabaya in realizing high madrasah. Design/methods/approach – This research is a case study. It used both primary and secondary data. The primary data were obtained through observations and interviews with the headmaster and teachers at MAN Surabaya. Findings –The important findings of this article show that there are two flagship programs academic and non-academic innovation implemented to realize State Islamic Senior High School Surabaya as an advanced, high-quality, and globally competitive madrasah. The performance assessment of teachers at State Islamic Senior High School Surabaya is carried out through the stages of planning, implementation, and evaluation. All processes are conducted in accordance with the regulations of the Ministry of Religious Affairs of the Republic of Indonesia. The teacher performance assessment has a significant impact, including increasing work motivation, strengthening professional relationships, and improving the overall quality of teaching and education. Research implications/limitations – The implication of this study lies in enriching the body of knowledge on the performance assessment of Islamic Education teachers in realizing high-quality madrasahs. However, this research has a limitation in that it was conducted only at the State Islamic Senior High School Surabaya and only covered a single performance period in 2024. Originality/value – This study provides empirical evidence on the performance assessment of Islamic education teachers. Future research could extend this framework to other performance assessment contexts.